2015
DOI: 10.1002/jmv.24099
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infections in Mexican women with normal cytology, precancerous lesions, and cervical cancer: Type-specific prevalence and HPV coinfections

Abstract: The prevalence and genotype distribution of human papillomavirus (HPV) provides the basis for designing HPV prevention programs. The prevalence rates of type-specific HPV and coinfections in samples of Mexican women were investigated in 822 women aged 18-87 years. HPV detection was performed using a Linear Array™ genotyping test. HPV infection was found in 12.4% of controls, 46.3% of those with cervical intraepithelial neoplasia 1, and 100% of those with cervical intraepithelial neoplasia 3 or cervical cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 78 publications
8
30
1
2
Order By: Relevance
“…On the other hand, Aguilar-Lemarroy et al, in an analysis of 822 samples, found HPV16 to be the most prevalent type in all the studied groups, as in the study by Salcedo et al 21 , but also identified HPV18, HPV45, HPV52, HPV58, and HPV39 types 22 .…”
Section: Concurrent Infectionsmentioning
confidence: 58%
See 1 more Smart Citation
“…On the other hand, Aguilar-Lemarroy et al, in an analysis of 822 samples, found HPV16 to be the most prevalent type in all the studied groups, as in the study by Salcedo et al 21 , but also identified HPV18, HPV45, HPV52, HPV58, and HPV39 types 22 .…”
Section: Concurrent Infectionsmentioning
confidence: 58%
“…It should be noted that HPV16 was only found in three coinfections and HPV18 was not found at all. Aguilar-Lemarroy et al also found HPV16 more frequently, associated in coinfection with types 18, 39, and 70 in samples from cervical cancer 22 . Remarkably, none of the samples in our study contained any of the high-risk HPV types, including single, double, and triple infections.…”
Section: Concurrent Infectionsmentioning
confidence: 89%
“…In 2015, HPV16 presented the highest frequency in cervical tumors (57%), while HPV18 showed a minor frequency (< 8%) in agreement with HPV incidence worldwide [4]. Nevertheless, HPV types 31, 45, 52, and 58 were also detected in Mexican females, suggesting an important and unattended factor for CeCa and HPV infection control [4,5].…”
Section: Introductionmentioning
confidence: 68%
“…In Northeast Brazil, HPV62 prevalence among the overall population was of 3.6% and in Korea, 2% of atypical squamous cell and low-grade squamous intraepithelial lesions were HPV62 positive [32, 33]. In Mexico, a IMSS Research Network report on HPV, including 822 women, found HPV62 infection in 3.1% of women without cervical lesions, in 5.1% with CIN1, in 6.7% with CIN3 and in 0.8% in CC samples [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The E6 (447 bp), E7 (291 bp) and L1 (1512 bp) genes from this HPV62 reference genome (8092 bp) encode for 148, 96 and 503 amino acid proteins, respectively. In a first report including cervical samples from mexican population, HPV62 was mainly detected in coinfection with other HPV genotypes and it was found in 5.1% of HPV positive patients with Cervical Intraepithelial Neoplasia Grade 1 (CIN1) and in 0.8% of HPV positive patients with CC using Linear Array HPV Genotyping test [14]. The aim of this study, was to determine the prevalence of this genotype in a greater number of samples among Mexican women and to detect possible mutations in L1, E6 and E7 genes of the HPV62 circulating in the Mexican population.…”
Section: Introductionmentioning
confidence: 99%